Increasing the precision of the hydrocylinder deep hole’s machining based on simulations of the errors formation process - Gorelova, Asia; Kristal, Mark (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
A new mathematical model is proposed where faceting pattern formation is treated as a consequence of the hole’s axis technologically inherited straightness error. The analysis of the model allowed to establish that the straightness error delta of the hole’s axis primarily determines the faceting pattern formation process. Theoretical assumptions are in agreement with the results of computer modeling of the shape formation during the finish boring of the crane boom extension hydrocylinder. An improved method for errors minimization is developed. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)